Improving the Solubility and Oral Bioavailability of a Novel Aromatic Aldehyde Antisickling Agent (PP10) for the Treatment of Sickle Cell Disease - Tarek A. Ahmed; Khalid M. El-Say; Fathy I. Abd-Allah; Abdelsattar M. Omar; Moustafa E. El-Araby; Yosra A. Muhammad; Piyusha P. Pagare; Yan Zhang; Khadijah A. Mohmmad; Osheiza Abdulmalik; Martin K. Safo (Pharmaceutics, 2021)
Background: Aromatic aldehydes, with their ability to increase the oxygen affinity of sickle hemoglobin, have become important therapeutic agents for sickle cell disease (SCD). One such compound, voxelotor, was recently approved for SCD treatment. Methyl 6-((2-formyl-3-hydroxyphenoxy)methyl) picolinate (PP10) is another promising aromatic aldehyde, recently reported by our group. Like voxelotor, PP10 exhibits O2-dependent antisickling activity, but, unlike voxelotor, PP10 shows unique O2-independent antisickling effect. PP10, however, has limited solubility. This study therefore aimed to develop oral and parenteral formulations to improve PP10 solubility and bioavailability. Methods: Oral drug tablets with 2-hydroxypropyl beta cyclodextrin (HP-β-CD), polyvinylpyrrolidone, or Eudragit L100-55 PP10-binary system, and an intravenous (IV) formulation with d-α-tocopherol polyethylene glycol 1000 succinate (TPGS) or HP-β-CD, were developed. The pharmacokinetic behavior of the formulations was studied in Sprague-Dawley rats. PP10, a methylester, and its acid metabolite were also studied in vitro with sickle whole blood to determine their effect on Hb modification, Hb oxygen affinity, and sickle red blood cell inhibition. Results: Aqueous solubility of PP10 was enhanced ~5 times with the HP-β-CD binary system, while the TPGS aqueous micelle formulation was superior, with a drug concentration of 0.502 ± 0.01 mg/mL and a particle size of 26 ± 3 nm. The oral tablets showed relative and absolute bioavailabilities of 173.4% and 106.34%, respectively. The acid form of PP10 appeared to dominate in vivo, although both PP10 forms demonstrated pharmacologic effect. Conclusion: Oral and IV formulations of PP10 were successfully developed using HP-β-CD binary system and TPGS aqueous micelles, respectively, resulting in significantly improved solubility and bioavailability.